From outsourcing logistics towards interactive learning in the supply chain: drivers, bottlenecks, enablers, and spatial effects - Evert-Jan Visser (European Regional Science Association (ERSA), 2004)
This paper focuses on factors driving, hindering and enabling a transformation of arm's length outsourcing linkages in supply chains into strategic partnerships between MNEs and core logistic service providers, and on the effects for logistic product and process innovation, the spatial structure of supply chains, and the location preferences of innovating logistic companies. In a setting of deregulation, globalisation, technological change in transport and communication, and ongoing changes in consumer demand, MNEs and their logistic specialists may engage in strategic partnerships so as to develop the competences required to effectively manage global supply chains with a view to lower costs and enhancing service. This introduces problems of governance and competence, however, and therewith, transaction costs (Coase 1991, Williamson 1985, Nooteboom 1999), power, trust (Nooteboom 2002), learning-by-interaction (Nooteboom 1992, 2000), lock-in and path dependence (Boschma, Frenken & Lambooy 2002). This paper investigates the relevance of these factors in the case of the development of a partnership between a Netherlands-based global logistic service provider and several of its clients. Case-study evidence is thus used for developing an integrated theoretical framework fit to study the commercial, logistic and spatial effects of current developments in the logistic service industry.
Keywords: 330